2003
DOI: 10.1682/jrrd.2003.10.0099
|View full text |Cite
|
Sign up to set email alerts
|

Using an evidence-based protocol to guide rehabilitation and weaning of ventilator-dependent cervical spinal cord injury patients

Abstract: Abstract-An evidence-based clinical protocol was developed to improve ventilatory muscle strength and endurance of ventilator-dependent cervical spinal cord injury (SCI) patients. The goal was to help these patients discontinue mechanical ventilation. The protocol, based on findings from other studies in the literature, consisted of pretraining optimization, as well as progressive resistance and endurance training. Following the protocol, mean maximal inspiratory pressure for low tetraplegic patients improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…11 Furthermore, the success rate is even better if we eliminate from this figure the patients in whom weaning is impossible because of the degree of severity of SCI (29 out of 35, 82.8%). The weaning process in our patients is slow because of the need of retraining and strengthening of the undamaged respiratory muscles (in our series, average was 47.3 days, median 25, versus 29 days of average in patients with neuromuscular diseases 10 or 12.5-15 days in unselected patients), 16,17 and it is similar to other series of SCI patients (26.6-56 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Furthermore, the success rate is even better if we eliminate from this figure the patients in whom weaning is impossible because of the degree of severity of SCI (29 out of 35, 82.8%). The weaning process in our patients is slow because of the need of retraining and strengthening of the undamaged respiratory muscles (in our series, average was 47.3 days, median 25, versus 29 days of average in patients with neuromuscular diseases 10 or 12.5-15 days in unselected patients), 16,17 and it is similar to other series of SCI patients (26.6-56 days).…”
Section: Discussionmentioning
confidence: 99%
“…Some experiences in SCI patients have shown promising results. [9][10][11][12] With this study, we have tried to evaluate the outcome of the IRCU of our hospital during 2.5 years, with the goal of establishing its efficacy in the treatment and follow-up of patients with respiratory failure due to SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent hypoxia has interesting implications as a possible therapeutic approach to humans with chronic cervical SCI. For example, after SCI, it may be that respiratory function along residual neural pathways can be enhanced after a relatively innocuous respiratory maneuver, and that physical therapy aimed at strengthening respiratory muscle performance (Gutierrez et al, 2003) may be facilitated by previous administration of intermittent hypoxia to strengthen residual synaptic pathways.…”
Section: Functional Significancementioning
confidence: 99%
“…We chose to have both groups adhere to a protocol because it was previously shown that having a designated protocol allows people with SCI to gradually improve endurance and strength, which leads to better outcomes. 20 We did not achieve the anticipated enrollment due to lower than expected admissions of individuals meeting the study criteria, and this decreased the statistical power of the study. This study cannot be considered a definitive trial on the efficacy of one Vt strategy or the other but does provide important information on the duration of weaning and the safety of using higher Vts in patients with subacute SCI.…”
Section: Discussionmentioning
confidence: 98%